Numerical simulation and evaluation of Campbell running and gating systems - Papanikolaou, Michail; Pagone, Emanuele; Jolly, Mark R.; Salonitis, Konstantinos (MDPI, 2020)
The most common problems encountered in sand casting foundries are related to sand inclusions, air, and oxide films entrainment. These issues can be addressed to a good extent or eliminated by designing proper running systems. The design of a good running system should be based on John Campbell’s “10 casting rules”; it should hinder laminar and turbulent entrainment of the surface film on the liquid, as well as bubble entrainment. These rules have led to the establishment of a group of components such as high and low placed filters (HPF/LPF) and standard gate designs such as the trident gate (TG) and vortex gate (VG) which are incorporated in wellperforming running system designs. In this study, the potential of the aforementioned running system designs to eliminate air entrainment and surface defects has been investigated via means of computational fluid dynamics (CFD) simulations. The obtained results suggest that the use of filters significantly enhances the quality of the final cast product; moreover, all of the gating system designs appear to perform better than the basic running system (BRS). Finally, the five in total running and gating system designs have been evaluated with respect to their ability to produce good quality cast products (reduced air entrainment and surface defects) and their sustainability component (runner scrap mass).
Keywords: Campbell running systems; sustainability; CFD